Peran Ekonomi Mikro Islam dalam Penguatan UMKM Syariah di Indonesia - Syakila Novia Fitri; Astri Hanum Lubis; Sopia Mayang Sari (Jurnal Deflasi, 2025)
This study aims to analyze the role of Islamic microeconomics in strengthening Sharia-based Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Islamic microeconomics, through institutions such as Baitul Maal wat Tamwil (BMT), contributes significantly by providing Sharia-compliant financing and empowering MSME actors. This study uses a descriptive qualitative approach by reviewing the latest literature, Sharia financing data, and national policies related to MSME development. The research findings show that financing based on Sharia contracts such as mudharabah, murabahah, and ijarah offers a more inclusive and fair alternative, thereby increasing the productivity, capacity, and competitiveness of MSMEs. Data from KNEKS and the Ministry of Finance show a significant increase in Sharia financing from 2023 to 2024. These findings confirm that Islamic microeconomics not only drives the growth of the real sector but also strengthens the economic independence of the Muslim community. This study recommends the development of innovative financial products, increasing Sharia financial literacy, and strengthening the digital service system to support the sustainable growth of Sharia MSMEs in the future.